Evaluasi Laporan Realisasi Anggaran berdasarkan PSAP No. 02 di Kantor Camat Langowan Selatan - Kolamban, Chelchia Vilia; Pangerapan, Sonny; Mawikere, Lidia M. (Yayasan Widyantara Nawasena Raharja, 2025)
Government accounting standards (SAP) set out the rules for preparing and presenting financial reports for all levels of government. Government accounting standards are clearly regulated in Government Regulation Number 71 of 2010. The South Langowan Subdistrict Office has presented a budget realization report. The purpose of this research is to evaluate how financial reports have been prepared based on PSAP No. 02 and Government Regulation Number 71 of 2010 concerning Government Accounting Standards. This research uses a descriptive qualitative method with a purposive sampling technique. The results of this research definitively show that budget realisation reports at the South Langowan Head Office have been made in accordance with Government Regulation No. 71 of 2010 concerning Government Accounting Standards PSAP No. 02.